2021
DOI: 10.1155/2021/5540173
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Regioselective Synthesis and 2D-NMR Studies of New 1,2,3-Triazole Compounds Derived from Acridone

Abstract: A simple and mild protocol towards the synthesis of new 1,2,3-triazole compounds derived from acridone has been developed via regiospecific 1,3-dipolar cycloaddition reaction between 10-(prop-2-yn-1-yl)acridone derivatives and aromatic azides using CuI as a catalyst. The cycloaddition reaction has been performed using conventional as well as microwave-assisted methods. Microwave-assisted synthesis caused a significant reduction in the reaction times and improvement in the yields of all the synthesized compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Both traditional and microwave-assisted techniques were used for the synthesis of compounds and under microwave heating the product was obtained in excellent yields in 10 min. 32 Alves et al reported the synthesis of the 4-aryl-1,4-dihydrochromene-triazoles 42 (Scheme 9) in an environmentally friendly 'one-pot' method without the need for metals, with PEG400 as the solvent. Starting with easily accessible building blocks, triazole derivatives were produced using microwave irradiation in 10 min with yields of 24-34%.…”
Section: Review Synopenmentioning
confidence: 99%
See 1 more Smart Citation
“…Both traditional and microwave-assisted techniques were used for the synthesis of compounds and under microwave heating the product was obtained in excellent yields in 10 min. 32 Alves et al reported the synthesis of the 4-aryl-1,4-dihydrochromene-triazoles 42 (Scheme 9) in an environmentally friendly 'one-pot' method without the need for metals, with PEG400 as the solvent. Starting with easily accessible building blocks, triazole derivatives were produced using microwave irradiation in 10 min with yields of 24-34%.…”
Section: Review Synopenmentioning
confidence: 99%
“…Both traditional and microwave-assisted techniques were used for the synthesis of compounds and under microwave heating the product was obtained in excellent yields in 10 min. 32…”
Section: Synthesis Of 123-triazole Hybridsmentioning
confidence: 99%